Propaganda and international relations: an outlook in wartime - Marsili, M. (Artciencia.com, 2015)
The aim of this essay is to highlight the role of propaganda during the conflicts in the contemporary age, particularly during the two World Wars. The propaganda developed during two major conflicts of the ‘900 as a true ‘weapon’ and instrument of government policy in international relations, has perfected the techniques of ‘news management’, and today is a real and relished ‘art’ applied to guide public opinion in favor of government decisions.